COMPARISON OF ENDOSCOPIC AND CONSERVATIVE MANAGEMENT IN PEDIATRIC VESICOURETERAL REFLUX: A RETROSPECTIVE STUDY - Memeti, Shaban; Kamiloski, Marjan; Ceku, Gani; Cvetanovska, Vesna; Lumani Bakiij, Njomza; Sulejmani, Haris; Risteski, Toni (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Background: Vesicoureteral reflux (VUR) is a prevalent congenital urinary tract anomaly in children, often associated with recurrent urinary tract infections (UTIs), renal scarring, and long-term complications such as hypertension and chronic kidney disease. The optimal management of primary VUR—particularly in intermediate grades—remains debated, with both conservative and endoscopic treatments widely used.  Objective: To compare clinical and functional outcomes of endoscopic injection therapy versus conservative management in pediatric patients with primary VUR, focusing on reflux resolution, UTI recurrence, renal scarring, and renal function.  Methods: This retrospective study included 70 pediatric patients with primary VUR treated at a tertiary center between 2015 and 2018. Thirty-five patients underwent endoscopic subureteric injection with dextranomer/hyaluronic acid copolymer, and 35 received conservative management with antibiotic prophylaxis. Comparative analysis assessed changes in VUR grade, recurrence of UTIs, renal scarring (via technetium-99m dimercaptosuccinic acid [DMSA] scintigraphy), renal function by kidney side, and serum creatinine levels.  Results: Endoscopic treatment achieved complete reflux resolution in 74.3% of cases. A significant reduction in reflux grade and improvement in right kidney function were observed in the intervention group (p < 0.001). The conservative group showed higher rates of recurrent febrile UTIs and no significant improvement in renal function. Renal scarring was present in both groups but slightly less frequent following endoscopic therapy. Post-treatment left kidney function was significantly higher in the conservative group (p = 0.020), likely reflecting baseline differences.  Conclusions: Endoscopic injection therapy is a safe and effective treatment for moderate-to-high-grade VUR in children, associated with superior reflux resolution and better infection control compared to conservative management. Conservative therapy remains appropriate for select low-grade cases but may confer higher risk for recurrent infections and limited renal recovery. Individualized treatment selection is essential to optimize pediatric VUR outcomes.   Keywords: vesicoureteral reflux, endoscopic therapy, urinary tract infection, renal scarring, pediatric urology, reflux resolution